Psycholinguistic Analysis of the Structure of the Association Area of the Stimulus Competence - Tamara Sharavara; Anatolii Kotsur; Nataliia Syzonenko; Yanina Tahiltseva (Психолінгвістика, 2018)
The article deals with the analysis of the association area structure of the notion of competence based on the results of the free association experiment. It was found out that respondents verbalize both key components of the lexicographical and terminological meaning of the notion (awareness, experience, skills, knowledge, mind) and its axiological component (politeness, correctness, professionalism, responsibility, respect). Some reactions testify to the process of identifying competence with the professional sphere of activity (profession, job).